Effects of solution conditions on methionine oxidation in albinterferon alfa‐2b and the role of oxidation in its conformation and aggregation. Issue 2 (30th November 2012) - Chou, Danny K.; Krishnamurthy, Rajesh; Manning, Mark Cornell; Randolph, Theodore W.; Carpenter, John F.
Abstract Physical and chemical degradation of therapeutic proteins can occur simultaneously. In this study, our first objective was to investigate how solution conditions that impact conformational stability of albinterferon alfa‐2b, a recombinant fusion protein, modulate rates of methionine (Met) oxidation. Another objective of this work was to determine whether oxidation affects conformation and rate of aggregation of the protein. The protein was subjected to oxidation in solutions of varying pH, ionic strength, and excipients by the addition of 0.02% tertiary‐butyl hydroperoxide (TBHP). The rate of formation of Met‐sulfoxide species was monitored by reversed‐phase high‐performance liquid chromatography and compared across solution conditions. Albinterferon alfa‐2b exhibited susceptibility to Met oxidation during exposure to TBHP that was highly dependent on solution parameters, but there was not a clear correlation between oxidation rate and protein conformational stability. Met oxidation resulted in significant perturbation of both secondary and tertiary structure of albinterferon alfa‐2b as shown by both far‐ultraviolet (UV) and near‐UV circular dichroism. Moreover, oxidation of the protein caused a noticeable reduction in the protein's resistance to thermal denaturation. Surprisingly, despite its negative effect on solution structure and conformational stability, oxidation actually reduced the protein's aggregation rate during agitation at room temperature as well as during quiescent incubation at 40°C. Oxidation of the protein resulted in improved colloidal stability of the protein, which is manifested by a more positive B22 value in the oxidized protein. Thus, the reduced aggregation rate after oxidation suggests that increased colloidal stability of oxidized albinterferon alfa‐2b counteracted oxidation‐induced decreases in conformational stability. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:660–673, 2013